Altered vertebral and femoral bone structure in juvenile offspring of microswine subject to maternal low protein nutritional challenge. Issue 11 (4th June 2019) - Lanham, Stuart A.; DuPriest, Elizabeth; Kupfer, Philipp; Cooper, Cyrus; Bagby, Susan P.; Oreffo, Richard O. C.
Abstract: Epidemiological studies suggest skeletal growth is programmed during intrauterine and early postnatal life. We hypothesize that bone development may be altered by maternal diet and have investigated this using a microswine model of maternal protein restriction (MPR). Mothers were fed a control diet (14% protein) or isocaloric low (1%) protein diet during late pregnancy and for 2 weeks postnatally. Offspring were weaned at 4 weeks of age to ad lib or calorie‐restricted food intake groups. Femur and vertebra were analysed by micro computed tomography in offspring 3–5 months of age. Caloric restriction from 4 weeks of age, designed to prevent catch‐up growth, showed no significant effects on bone structure in the offspring from either maternal dietary group. A maternal low protein diet altered trabecular number in the proximal femur and vertebra in juvenile offspring. Cortical bone was unaffected. These results further support the need to understand the key role of the nutritional environment in early development on programming of skeletal development and consequences in later life. Abstract : Epidemiological studies suggest skeletal growth is programmed during intrauterine and early postnatal life. A maternal low protein diet altered trabecular number in the proximal femur and vertebra in juvenile offspring.